2009
DOI: 10.1080/14739879.2009.11493812
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Attitudes to General Practice Registrars: A Review of the Literature

Abstract: Introduction With the population ageing, it is imperative for training practices to provide GP registrars with sound experience in managing the health problems of older persons, especially chronic conditions. However, it is reported that a significant proportion of these patients will be resistant to consulting registrars, with concerns regarding disruption of continuity of care being a significant factor. The challenge for training practices is to identify approaches to engage registrars in the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Patients do not always want to consult a trainee for various reasons, for instance chronic or emotional problems were found to be associated with reduced willingness to consult registrars 46. Also, in another study, medical receptionists reported that patients with complex conditions were relatively more often assigned to the trainer 31…”
Section: Discussionmentioning
confidence: 99%
“…Patients do not always want to consult a trainee for various reasons, for instance chronic or emotional problems were found to be associated with reduced willingness to consult registrars 46. Also, in another study, medical receptionists reported that patients with complex conditions were relatively more often assigned to the trainer 31…”
Section: Discussionmentioning
confidence: 99%
“…The limited data from similar training systems in Australia and the UK also suggested their GPRs’ exposure to older patients was less than that for established GPs . A number of reasons for this have been proposed, including older patients’ desire for continuity of care with their usual GPs , older patients not understanding the role of GPRs and older patients not being aware of GPRs’ previous training or experience , supervision arrangements or time they will spend in a practice . Reduced exposure to older patients may also result from structural factors within training practices which result in GPRs being allocated lower complexity presentations .…”
Section: Introductionmentioning
confidence: 99%
“…Of further concern is evidence that even when GPRs do consult older patients, the consultation content may be superficial. Patient‐based interview and survey data suggest that older patients may treat GPR consultations as a stop‐gap measure, for example for a prescription repeat, until they can consult their regular GP to address management concerns . In addition, it appears that patients’ desire to keep chronic disease management with their regular GP increases with the complexity of older patients’ health problems , supported by data demonstrating reduced rates of consultation between GPRs and patients with chronic disease in comparison with established GPs .…”
Section: Introductionmentioning
confidence: 99%
“…In order for nurses to be effective in the collaborative management of chronic disease in Australia it is necessary that they are seen as providing reliable health information. A recent study found that older adults' reluctance to have GP registrars manage their chronic conditions could be countered by maintaining a relational link with their regular GP [30] . Models such as this should be investigated to see whether they can be extended to Practice Nurses, allowing nurses to contribute optimally to the primary health care team whilst also helping to alleviate pressure on GPs.…”
Section: Perceived Reliabilitymentioning
confidence: 99%